Endocytic Uptake of Solid Lipid Nanoparticles by the Nasal Mucosa - Ammar S. Al Khafaji; Maureen D. Donovan (MDPI AG, 2021)
Nanoparticles may provide unique therapeutic opportunities when administered via the nasal cavity, yet the primary uptake and transfer pathways for these particles within the nasal mucosa are not well understood. The endocytic pathways involved in the uptake of fluorescently labeled, (Nile Red) solid lipid nanoparticles (SLNs) of different sizes (~30, 60, and 150 nm) were studied using excised bovine olfactory and nasal respiratory tissues. Endocytic activity contributing to nanoparticle uptake was investigated using a variety of pharmacological inhibitors, but none of the inhibitors were able to completely eliminate the uptake of the SLNs. The continued uptake of nanoparticles following exposure to individual inhibitors suggests that a number of endocytic pathways work in combination to transfer nanoparticles into the nasal mucosa. Following exposure to the general metabolic inhibitors, 2,4-DNP and sodium azide, additional, non-energy-dependent pathways for nanoparticle uptake were also observed. While the smallest nanoparticles (30 nm) were the most resistant to the effects of pharmacologic inhibitors, the largest (150 nm) were still able to transfer significant amounts of the particles into the tissues. The rapid nanoparticle uptake observed demonstrates that these lipid particles are promising vehicles to accomplish both local and systemic drug delivery following nasal administration.